Effect of Magnetic Field on Non-Periodic Flow of Fluid between Two Concentric Cylinders - Ankita Baranwal; Dr. Ashish Kumar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study investigates the unsteady flow of a dusty fluid, incorporating thermal conduction, around a circular cylinder. The dusty fluid model considers a two-phase system consisting of a carrier fluid and suspended solid particles, with interactions such as drag and heat transfer between phases. The governing equations, including continuity, momentum, and energy equations for both phases, are formulated and solved under appropriate initial and boundary conditions. Analytical and numerical techniques are employed to capture the transient behavior of the system. Key parameters, such as the dust particle concentration, thermal conductivity, and unsteadiness factor, are analyzed for their influence on the velocity and temperature fields. The results reveal that dust particles significantly alter the flow and heat transfer characteristics around the cylinder, which has practical implications in engineering fields such as chemical reactors, environmental engineering, and aerosol technology.
Keywords: Dusty fluid; unsteady flow; thermal conduction; circular cylinder; fluid mechanics; Navier-Stokes equations